Determinação de elementos-traço em amostras de nitreto de alumínio e nitreto de silício por análise direta de amostras sólidas em espectrometria de absorção atômica com forno de grafite - Mattos, Julio Cezar Paz de (2008)
A graphite furnace atomic absorption spectrometry method using direct solid sampling has been developed for the determination of Cr, Cu, Fe, K, Mn, Sb and Zn in powdered AlN and Si3N4. Owing to the vaporization of AlN during atomization step, different approachs to avoid the interferences caused by high background arising from matrix thermal decomposition, were investigated. A comparison between the performance of deuterium background correction system and the based on Zeeman effect for the analysis of AlN sample was carried out. For silicon nitride analysis, although during atomization of all analytes, excluding Zn, conversion of Si3N4 into Si0 and SiC was taking place and its essential part vaporized as different species, no problems the resultant background was properly corrected. The calibration for both samples was carried out using aqueous standard solutions. In the determination of Fe in Si3N4 powders, graphite powder was used in order to achieve quantitative vaporization and also to increase the lifetime of the platform, this procedure was also advantageous for the determination of Cr and Cu. During AlN analysis, the application of graphite or other chemical modifiers was unnecessary. For AlN analysis, it was possible to apply sample amounts up to 16 mg for Sb, the relative standard deviations (n = 5) were between 2 and 16%. The Achieved limits of detection were between 7 (Sb and Zn) and 2000 ng g-1(Fe). During Si3N4 analysis sample masses up to 2 mg could be applied per analysis cycle, the relative standard deviations (n = 5) were between 5 and 18% (n = 5). For the most sensitive conditions, limits of detection between 0.1 (Zn) and 213 ng g-1 (Fe) are achievable for the analysis of Si3N4. The accuracy was checked by comparison of the results with those obtained using other methods including neutron activation analysis whereby good to reasonable agreement was achieved.